Multifunctional Deep Eutectic Solvent-Based Microemulsion for Transdermal Delivery of Artemisinin - Li, Menghan (Langmuir : the ACS journal of surfaces and colloids, 2024)
As a serious public health issue, malaria threatens the health of millions of people. Artemisinin, a gift from traditional Chinese medicine, has been used in the treatment of malaria and has shown good therapeutic efficiency. However, due to its low solubility, poor bioavailability, and short half-life time, some smart delivery strategies are still required. Herein, a multifunctional DES prepared from ibuprofen and menthol was prepared. This DES was shown to efficiently promote the solubility of artemisinin up to 400-fold. Then, it was further applied as the oil phase to construct an O/W microemulsion with the help of Tween-80 + Span-20 mixed surfactants. The prepared microemulsion displayed high efficiency in improving the permeability of artemisinin, which can be ascribed to the presence of the permeation enhancer menthol in DES and the microstructure of the O/W microemulsion. Moreover, the simultaneous permeation of artemisinin and ibuprofen further indicated the potential benefits of the presented formulation in the treatment of malaria. To sum up, the microemulsion based on multifunctional DES presented herein provided an effective method for transdermal delivery of artemisinin